EFFECT OF DISCHARGE VARIATION ON THE PERFORMANCE OF SINGLE BLADE ARCHIMEDES SCREW TURBINE: PREDICTION WITH COMPUTATIONAL FLUID DYNAMIC - Gunawan Rudi Cahyono; Apip Amrullah; Pathur Razi Ansyah; N. Alexius Mikael; P.S.M. Reynaldi; Rusdi Rusdi (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2021)
Constructing a small-scale hydroelectric power station that can run efficiently at a head lower than 10 m is one possible method for reducing the impact of the electricity crisis in remote areas of Indonesia. The Archimedes Screw turbine is one type of turbine that is ideal for discharges below 10 m. In this study, the simulation results show that the value of Turbulences Kinetic Energy is directly proportional to the increase in flow rate but inversely proportional to the level of immersion. This type of turbine is unless well in Indonesia due to a lack of information regarding the application of low head power plants. The turbine model that is suitable for the low head is investigated in this study. Before being tested, the turbine is first designed theoretically and then numerically evaluated. With discharges of 1 l/s, 2 l/s, and 3 l/s and turbine immersion levels of 30%, 50%, and 70%, ANSYS CFD (Computational Fluid Dynamic) software was used to investigate flow rate and level of immersion in the turbine. According to the investigation findings, the discharge has a considerable impact on the turbine's movement; the higher the flow rate, the higher the power to the turbine, which produces a torque on the turbine. The simulation findings indicate that the value of Turbulence Kinetic Energy is proportional to the increase in flow rate but inversely proportional to the level of immersion.